2023
DOI: 10.55563/clinexprheumatol/970881
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of idiopathic inflammatory myopathies during the COVID-19 pandemic: a single-centre experience

Abstract: ObjectiveHigher-level evidence is required to discern whether the incidence of idiopathic inflammatory myopathies (IIM) has increased during the COVID-19 pandemic and whether the disease pattern and course have changed. We aimed to analyse patients who were diagnosed with IIM at our tertiary care centre during the pandemic and compare them with IIM patients diagnosed before COVID-19. MethodsWe retrospectively analysed the medical records of adult patients (>18 years) who were diagnosed with IIM during COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Furthermore, they observed that the newly diagnosed patients displayed different demographic characteristics and more severe course of the disease than that observed before the pandemic, although the prognosis remained unchanged. They suggested that both the SARS-CoV-2 infection and SARS-Cov-2 mRNA vaccines could have been possible triggers for IIMs appearance (1). Their observation is surely interesting and in line with the common idea of a possible link between infections and the development of autoimmunity (2), particularly, between viruses and IIMs.…”
mentioning
confidence: 59%
“…Furthermore, they observed that the newly diagnosed patients displayed different demographic characteristics and more severe course of the disease than that observed before the pandemic, although the prognosis remained unchanged. They suggested that both the SARS-CoV-2 infection and SARS-Cov-2 mRNA vaccines could have been possible triggers for IIMs appearance (1). Their observation is surely interesting and in line with the common idea of a possible link between infections and the development of autoimmunity (2), particularly, between viruses and IIMs.…”
mentioning
confidence: 59%
“…Recently, an increased incidence of IIMs was reported during the COVID-19 pandemic ( 33 , 34 ). It has been postulated that an overactive innate immune response to SARS-CoV-2 might contribute to the development and deterioration of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested a potential correlation between onset or flares of IIM with COVID-19 infection and/or vaccination (30)(31)(32). Literature demonstrates a detrimental effect of the pandemic on continuity of care for many patients with IIM, raising concern for risk of downstream effects on disease outcomes for patients as well (33,34).…”
Section: Mental Health In Paediatric and Adult Myositis-related Disea...mentioning
confidence: 99%